Floating power plant applications for electric battery using thermoelectric generators (TEG) on solar panels. Issue 1 (1st November 2022) - Zein, E; Safril, M; Sutanto, E; Hamid, M I; Aziz, M; Fahmi, F
Abstract: The use of solar energy as a source of electrical power is done by utilizing solar panels. Even though the sun has two sources of energy: light energy and heat energy, however, up to now, the heat energy generated by the sun is not yet fully utilized. This study was aimed to develop floating -on water- power plant where the temperature difference that occurs in thermoelectric generator can increase the optimal output voltage on solar panels. The thermoelectric hot side is patched under the solar panel, and the cold side is patched on the surface of the water level. This study showed that the highest voltage results on the connected series are 3±1 volts with thermoelectric generator connected 60 series. The power generated by the thermoelectric generator is 3-7mW with a temperature difference of 14.5°C. Thermoelectric efficiency of the floating generators was 84.4%. The electrical power generated by the thermoelectric generator was stored in a 3V 2000 mAh electric battery. This energy is sufficient to light up the lamps and to charge the mobile phone for daily use.